Flavonoids in atopic dermatitis: mechanisms, delivery innovations, and translational strategies - Li, Dongdong; Han, Yusheng; Zhou, Jingjing; Chen, Jing; Tey, Hong Liang; Tan, Timothy T. Y. (Frontiers in Pharmacology, 2025)
ObjectiveTo provide a comprehensive narrative synthesis of recent advances in the pharmacological actions and therapeutic potential of natural flavonoids in atopic dermatitis (AD), with emphasis on their multi-target pharmacological effects across core pathological mechanisms. The review also addresses pharmacokinetic limitations, formulation challenges, delivery innovations, safety concerns, and emerging clinical evidence to inform translational research and therapeutic development.MethodsThis narrative review is based on a targeted literature search of PubMed, Web of Science, ScienceDirect, and SpringerLink, covering English-language, peer-reviewed articles published between 2010 and 2025. Search terms included natural flavonoid metabolites (e.g., quercetin, baicalin, epigallocatechin-3-gallate [EGCG]) combined using Boolean operators (e.g., AND, OR) with keywords related to atopic dermatitis, its underlying mechanisms, and therapeutic interventions. Studies focusing on in vitro, in vivo, or clinical evaluations of mechanistic pathways, therapeutic potential, or delivery strategies were included, while those addressing synthetic flavonoids, non-AD models, or lacking mechanistic relevance were excluded. This review does not follow a systematic review protocol.ResultsNatural flavonoids exert multi-target effects in AD models by restoring skin barrier integrity, modulating immune and chemokine dysregulation, alleviating pruritus, regulating microbial homeostasis and programmed cell death, and attenuating oxidative stress. However, pharmacokinetic and physicochemical limitations such as poor solubility, low bioavailability, metabolic instability, and limited dermal targeting currently constrain clinical application. Potential safety concerns, including hepatotoxicity and endocrine disruption, also warrant careful evaluation. To address these challenges, advanced delivery platforms including microneedles, hydrogels, nanocarriers, microsponges, and liposomes have been explored to improve dermal delivery. Additionally, oral delivery systems developed in other inflammatory and oncological models provide valuable insights for guiding translational strategies in AD. Preliminary clinical evidence suggests potential benefits of flavonoid-based interventions; nevertheless, larger and well-controlled trials are necessary to substantiate their pharmacological effects and evaluate long-term safety.ConclusionNatural flavonoids exhibit multi-target effects in AD by modulating core pathological processes. Although challenges such as limited bioavailability and safety concerns continue to impede clinical translation, these limitations may be addressed through the optimization of delivery strategies, rigorous pharmacokinetic and toxicological assessments, mechanism-driven in vitro, in vivo, ex vivo studies, and well-designed clinical trials.